Industrial Capitalism and Its Paradoxes in Europe XVIII – XIX Century - LAPTEVA, E. V.; OSTROUMOV, V. V.; BOLDYREVA, S. Yu.; PROTOPOPOVA, N. I. (Journal of Advanced Research in Law and Economics, 2019)
Until the mid-eighteenth century the world economy was slowly evolving, but after the 1750-s a radical change occurred, which had a huge impact not only on the economy, but also on culture, society and life in general.  The industrial revolution became the main lever of change. As a result, its main economic component - agriculture - has ceased to be dominant. Traditionally, the industrial revolution was seen as a sequential event, a chain of events from the lowest to the highest. The author made an attempt to consider the main parameters of the industrial revolution as a chain of paradoxes characteristic of developed European countries. To do this, turning to classical works of a theoretical and scientific-practical nature, the authors tried to consider the problem of European countries entering the industrial stage as a complex, contradictory and difficult process that revealed both leaders and Laggards.